PENGARUH KREATIVITAS TERHADAP PERKEMBANGAN USAHA (KASUS SENTRA KERAJINAN ROTAN RUMBAI DI PEKANBARU) - Rani Nadia; Sri Zuliarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of research was to determine the effect creativity on business development Rotan handicraft center in Rumbai region. The research concludes that the soul of creativity within Rotan entrepreneurs who are in the center area Rotan Tassel is considered to be good. While business development Rotan tassel in Pekanbaru assessed sufficiently developed. The results of the data analyst by SPSS, creativity has a very strong, connection to the development of the business, with a correlation value of 0,831. It means that creativity variables provide a positive and significant effect on the variables of business development at Tassel Rotan craft, creativity is enhanced when variables that will lead to an increase in the variable business development.Keyword: creativity, business development, Tassel Rotan Rumbai